PENGARUH SISTEM PELAPORAN, AUDIT KINERJA, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Ni Wayan Windy Widyarini; Ni Wayan Alit Erlina Wati (UNHI Press, 2021)
Accountability in managing village funds is needed to be able to run village governance properly. Several factors affect the accountability of village fund management, including the reporting system, performance audits, and human resource competence. This study aims to determine the effect of the reporting system, performance audits, and human resource competence.This research was conducted at the Village Office in North District. The sample in this study were 40 employees, the sampling method used was purposive sampling. The data analysis technique used in this research is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test.The results showed that the reporting system variable had a positive and significant effect on the accountability of village fund management. Performance audits have a positive and significant effect on the accountability of village fund management. Human resource competence has a positive and significant effect on the accountability of village funds.